USING OF CONTOUR MAPS FOR PRESENTATION OF COMPOUND STATISTICAL TABULATE TO STUDY THE PERCENTAGE OF SUCCESS IN THE DEPARTMENT OF GEOLOGY AT THE UNIVERSITY OF BAGHDAD FOR THE PERIOD 1999-2008 - LAMYA Z. HUMMADY; AHMED SH. AL-BANNA (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Two and three dimension contour maps were constructed to exhibit the compound statistical tabulate, depending on surfer program application. The percentage of success in the department of geology at university of Baghdad for the period 1999-2008 is considered as an application of this approach. Surfer program maps show clearly the regional (long wavelength variation within many years and subjects) and local (short wavelength variation with certain year or subject) changes in the percentage of success in the department of geology. It is observed from the regional maps that the percentage of success decreased with the time progress, especially in the first attempt examination. At the same time many local variation were detected. It is believed that the administration decisions may be caused some local changes in certain years, while the other local observation may be related to teaching staff changes for certain scientific subjects